ETIKA DAN MORALITAS PENDIDIKAN DALAM MENGEMBANGKAN SDM BERBASIS SAINS DAN TEKNOLOGI - Sagala, Syaiful (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study aims to determine how the ethics and morality of education in developing human resources (HR) based on science and technology. This study designed case study using a descriptive qualitative approach with data collection techniques through Focus Group Discussion (FGD) and observation through school visits supported by documentation. The findings of this study indicate that schools that have the courage to face risks based on ethical values generally have managed to overcome routine problems and have been able to develop themselves become more productive and competitive. From these findings it is assumed that the quality of ethics and morality application in school management can be the basic foundation of the school to achieve the success of developing human resources based on science and technology in their respective schools.Keywords— Ethics, learning, human resource development